Role of viral infection in sudden hearing loss - Chen, Xin; Fu, Yao-yao; Zhang, Tian-yu (Journal of international medical research, 2019)
According to a recent epidemiological survey, the incidence of sudden sensorineural hearing loss (SSNHL) is increasing yearly. The cause of SSNHL is of great interest in research. To date, viral infection, vascular occlusion, abnormal cellular stress responses within the cochlea, and immune-mediated mechanisms are considered the most likely etiologies of this disease. Among these etiologies, the relationship between viral infection and sudden deafness has been unclear. In this review, we mainly discuss the viral hypothesis of SSNHL. There is little research proving or clearly indicating the pathogenesis of this disease. Further research is needed to elucidate the precise etiopathogenesis to better understand SSNHL and establish more suitable treatment to help restore hearing in affected patients.